GEOGRAPHIC INFORMATION SYSTEM AND ANALYTICAL HIERARCHY PROCESS FOR LAND USE PLANNING OF BEEKEEPING IN FOREST MARGIN OF BOGOR REGENCY, INDONESIA - Widiatmaka .; Wiwin Ambarwulan; Chandrasa E Sjamsudin; Lailan Syaufina (Jurnal Silvikultur Tropika, 2016)
One way to establish forest conservation is by improving the welfare of the community residing at the forests’ borders. Beekeeping has the potential to increase the income of the people around the forest. This study aims to delineate beekeeping zones bordering the forest regions. Multi-criteria analysis based geographic information system was used to delineate the ecologically suitable areas for honey bees. The parameters used included physical parameters (temperature, rainfall, distance from water source and altitude), economic parameters (distance from the roads and distance from the market) and social parameters (land use and distance from settlements). The parameters were weighed by applying analytical hierarchy process. The result was then inputted into a spatial model designed to determine the ecological suitability for honeybees. The suitable land for bees’ forages was delineated using land suitability analysis with maximum limitation method. The results of both analyses were then overlaid to delineate suitable areas for beekeeping. The analysis resulted in locating recommended areas for the cultivation of honey bees and forages around the forest periphery, by taken into account official spatial land use planning.Key words: Habitat suitability, land suitability, bee forage, land use planning